Proximity Relationship in Naming Friends' Telephone Numbers: A Socio-onomastic Analysis - Kristianti, Yuliana; Wijana, I Dewa Putu (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
Naming a friend's phone number can represent a friendship relationship between the owner of the phone number and the person who saves or names the phone number. This study analyzes the form, meaning, and function of naming a friend's phone number based on the closeness of the friendship using a socio-onomastics study. There were 39 data analyzed and classified based on the forms. The method used is qualitative descriptive and in-depth interviews with informants who are students of the Master of International Relations, University of Indonesia. The results of this study show that three layers of friendship can be reflected in the naming of phone numbers, namely close friends, regular friends, and acquaintances.